PENGGANTIAN JEMBATAN KALIGUNG TUWEL DENGAN MENGGUNAKAN KONSTRUKSI RANGKA BAJA - Gilar Taswindo; Wahyu Agung Nugroho; Moga Narayudha; Ilham Nurhuda (Jurnal Karya Teknik Sipil, 2014)
Kaligung Bridge is located in Tuwel village of Slawi in Tegal regency. The Bridge connects Bumijawa and Tuwel area and stretches along 70 meters above Kaligung river. In this project, Kaligung Tuwel bridge was designed as a steel truss system. The design steps are as follows : analysis of the existing conditions, design the upper structure and the substructure of the bridge, and calculate budget plan ( RAB ). The Design of the upper structure considers loads such as : self weight, dead load, traffic load, wind load, and seismic load. The design was carried out using LRFD (Load and Resistance Factor Design) method. Next, the substructure was designed by calculating the dimension of the foundation and abutment. The foundation was designed as a caisson while the abutment was of cantilever type.